Predicates of Indonesian and English Simple Sentences - Ingatan Gulö (Universitas Teknokrat Indonesia, 2017)
This paper was developed from a research report presented in The Third Southern Region of Sumatera TEFLIN held by Sriwijaya University in 2014. Comments recieved by the participants of the seminar and following studies done on the topic made it possible for this article to find its way to be published in a journal. As Indonesian and English sentences realize their predicates by using different kinds of syntactic categories, most learners of English having Indonesian as their linguistic background face difficulties in understanding the language. This is a contrastive study done by conducting an analytical analysis on simple sentences of both languages. The result of this research shows that both English and Indonesian sentences employ verbs as their predicates. However, in addition to verbs, Indonesian sentences also use other kinds of syntactic categories such as nouns, adjectives, etc. to be the predicates of sentences. These main differences of English and Indonesian systems have to be underlined in learning process and teaching English to learners in order to avoid grammatical mistakes.